Sagittal Alignment of Spine and Spinal Cord for Upper Cervical Irreducible Atlantoaxial Kyphosis in Elderly Patients. Issue 6 (July 2016) - Sasao, Yutaka; Kojima, Atsushi; Torii, Yoshiaki; Morioka, Shigeta; Fujii, Atsushi; Aoki, Haruhito
Abstract : Study Design: Retrospective study. Objective: To evaluate clinical and radiographic outcome of posterior decompression and occipito-cervical/thoracic (OCT) fusion in patients with irreducible atlantoaxial kyphosis (IAK). Summary of Background Data: Posterior OCT fusion is an effective surgical procedure for treating IAK in the elderly. However, it is unclear whether correction can be obtained by the strong corrective force provided by implants, even in patients in whom reduction cannot be obtained preoperatively. There are no reports of improvement in patients in whom correction could not be achieved by a rigid system. Methods: Twenty-five patients with IAK with mild vertical subluxation due to rheumatoid arthritis and 3 patients with IAK due to os odontoideum were treated with fossa magnum decompression, C1 laminectomy and OCT fusion. Results: Mean follow-up period was 4.2 years. Preoperative and postoperative neurological findings revealed improvement by 1 or more grades in 18 of 28 (64.2%) patients. The parameters of spinal alignment, sagittal spinal cord alignment, and basilar invagination were evaluated on radiographs. No significant difference between preoperative and postoperative status was seen for the clivo-axial angle, occipito-upper cervical angle, atlantodental interval, or occipito-cervical 2 angle, whereas significant improvement was seen in the cervico-medullary and dorsal CM angles (both P <0.05). No significant postoperative change in the vertical direction was seen for any of the parameters. Width of the spinal cord at the C1 level was significantly increased postoperatively, with a significant expansion of the cerebral spinal fluid space at the same level ( P <0.05). Conclusions: Posterior decompression with fusion for the treatment of IAK in the elderly did not produce significant change in spinal alignment, but did significantly improve spinal cord alignment and local spinal cord compression at the C1 level, achieving satisfactory clinical outcomes.